Students' Evaluation of their English Language Learning Experience - Muhamad, Maizatulliza; Kiely, R. (IAIN Samarinda, 2017)
In the field of English language teaching and learning, there is a long history of investigating students’ performance while they are undergoing specific learning programmes. This research study, however, focused on students’ evaluation of their English language learning experience after they have completed their programme. The data were gathered from 20 semi-structured interviews with 10 ‘good’ students and 10 ‘weak’ students emphasizing on factors which contributed to their proficiency level, preferred teaching approaches and learning strategies as well as their overall learning experience. The qualitative analysis indicated some different views between the ‘good’ and the ‘weak’ students in terms of their proficiency level and the contributing factors to their success (or lack of) in learning English. They however, shared similar opinion on preferred teaching approaches, learning strategies and classroom experience. The results have implications for pedagogy as they highlight some insights which may facilitate success in English language learning.